2022
DOI: 10.1097/ico.0000000000003110
|View full text |Cite
|
Sign up to set email alerts
|

Intrastromal Corneal Ring Segments Implantation After Deep Anterior Lamellar Keratoplasty for Astigmatism Correction: Mid-term and Long-term Follow-up

Abstract: The aim of this study was to assess the long-term outcomes of implanting intrastromal corneal ring segments (ICRSs) using a femtosecond laser for correcting astigmatism in patients who had previous deep anterior lamellar keratoplasty (DALK) throughout a 5-year follow-up period.Methods: This retrospective study included 40 eyes of 40 patients with previous DALK and astigmatism $3.00 D who underwent Ferrara-type ICRS implantation. The manifest refraction, uncorrected (UDVA) and corrected (CDVA) distance visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated the safety and efficacy of these procedures after DALK. [24][25][26][27] On the other hand, when performing a triple procedure, we suggest using a capsular tension ring to facilitate the exchange of the lens in case of an unexpected refractive result or a change in the donor button.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the safety and efficacy of these procedures after DALK. [24][25][26][27] On the other hand, when performing a triple procedure, we suggest using a capsular tension ring to facilitate the exchange of the lens in case of an unexpected refractive result or a change in the donor button.…”
Section: Discussionmentioning
confidence: 99%
“… Forest plot for visual acuity change using fixed- and random-effects model [ 5 , 6 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 ]. …”
Section: Figurementioning
confidence: 99%
“…Furthermore, novel progressive thickness ICRS (i.e., one end of the ring is thicker than the other end) has been successfully used to treat keratoconic eyes with non-uniform irregularities, resulting in a progressive corneal flattening effect ( 179 , 180 ). Recently, Alfonso-Bartolozzi et al ( 181 ) also reported using FSL-assisted, Ferrara-type ICRS to effectively correct astigmatism (≥3.00 D) following DALK.…”
Section: Surgical Treatmentmentioning
confidence: 99%